Analysis of some physical, chemical and microbiological aspects of honey samples produced and consumed in Turkey - Bakirdere , Sezgin; Yaroglu , Tolga; Tirik, Nihan; Demiroz, Mehmet; Karaca, Abdullah (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
Analysis of honey produced in the western part of Turkey was carried out in this study. Fifty honey samples, collected from the local market in this region were analyzed for their physicochemical parameters including hydroxymethylfurfural (HMF), electrical conductivity, sucrose, free acidity, moisture and water insoluble impurities, in addition to pathogenic microorganisms present. HMF amounts determined in 47 samples were found to be between 1.9 and 98.0 mg/kg with good reproducibilities (%RSD: 3.2% or better). There were no pathogenic microorganisms in any of the investigated samples. Electrical conductivity that gives information about their mineral contents was measured, and the mean value was found to be 0.33 mS/cm (N=34). In general, most of the samples were considered to meet the requirements of Turkish Food Codex and European Commission Directives.